Introducing Allergenic Food into Infants' Diets: Systematic Review. Issue 2 (March 2017) - Larson, Katelin; McLaughlin, Jessica; Stonehouse, Mallory; Young, Brittany; Haglund, Kristin
Abstract: Purpose: The purpose of this systematic review was to explore the association between timing of introduction of potentially allergenic foods to infants and development of food allergies. Methods: CINAHL, Medline, PubMed, Science Direct, and Web of Science were searched using the terms solid food, complementary food, or infant feeding combined with allergy or hypersensitivity for articles published in English in 2000 or later. Inclusion criteria were 1) primary research articles with 2) a focus on association between introduction of complementary foods including potentially allergenic foods into diets of infants less than 12 months of age and development of food allergies. Articles were excluded if they were 1) not primary research, 2) about complementary foods only (without specificity of allergenic foods), or 3) on allergic conditions other than food allergy (such as asthma or eczema). Results: The initial literature search yielded 533 articles; 14 articles met inclusion criteria. Level of evidence of each study was determined with the SORT criteria. Results found that delayed introduction of solid foods in general and allergenic foods in particular was not associated with decreased risk for allergic diseases among high and low-risk infants. Later introduction was associated with increased risk for allergy development. Clinical Implications: For infants at low risk for development of food allergies, providers should advise caregivers to introduce potentially allergenic foods with other solid foods between 4 and 6 months of age when children show an interest in eating solids. Infants at high risk for peanut allergy, should be evaluated by an allergy specialist prior to introduction of peanuts and work with providers to create an individualized plan for introduction of peanuts and other allergenic foods as needed. Abstract : Delaying introduction of potentially allergenic foods may have had unintended consequences of increasing prevalence of food allergies among children. A review of the evidence suggests early rather than delayed introduction may be the best option for low risk infants.